(untitled) (American Journal of Pedagogical and Educational Research, 2025)
This article discusses modern and convenient methods for improving the management of the quality of education in general secondary schools and makes proposals for implementing these mechanisms in practice. It promotes the use of innovative forms and methods of education in the educational process in general secondary schools.